1993
DOI: 10.1002/jcc.540140404
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a posteriori and a priori BSSE correction schemes for SCF intermolecular energies

Abstract: A systematic SCF study has been undertaken to compare the conventional a posteriori Boys-Bernardi BSSE correction scheme with our recent CHA/F method in which BSSE is excluded in a priori manner. Potential curves have been obtained for nine simple hydrogen-bonded systems by using nine different basis sets for each. It is concluded that the difference between the aposteriori BB and the apriori CHA schemes diminishes much faster when the basis set improves than BSSE disappears from the uncorrected SCF results. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…Similar to the observations in ref. 12, the largest differences could be found in the case of the 6-31G and DZV basis sets. In these cases, the CHA interaction energies fell between the BB-corrected and the uncorrected DFT values in agreement with the well-known fact that, when using small basis sets, the BB scheme tends to overcompensate 40 the BSSE.…”
Section: ( ) Comparison Of a Posteriori Bb And A ( ) Priori Cha Bsse mentioning
confidence: 88%
See 2 more Smart Citations
“…Similar to the observations in ref. 12, the largest differences could be found in the case of the 6-31G and DZV basis sets. In these cases, the CHA interaction energies fell between the BB-corrected and the uncorrected DFT values in agreement with the well-known fact that, when using small basis sets, the BB scheme tends to overcompensate 40 the BSSE.…”
Section: ( ) Comparison Of a Posteriori Bb And A ( ) Priori Cha Bsse mentioning
confidence: 88%
“…However, the same effect was also observed at the SCF level. 12 It must be emphasized that the TZV basis set, even without polarization functions, provided very small differences between the a priori-and a posteriori-corrected DFT models throughout the calculations, regardless of the system investigated. This is probably the smallest basis set that can be safely applied for the investigation of hydrogen-bonded complexes by using correlation methods.…”
Section: ( ) Comparison Of a Posteriori Bb And A ( ) Priori Cha Bsse mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the philosophy of CHA, one can exclude BSSE by preventing the changes of the orbitals (the appearance of delocalizations from one subunit to another) under the influence of pure intramolecular interactions. In what follows we shall introduce the CHA/F technique for the case of three subunits, by using an argumentation which differs formally, but not essentially from the previous one, which was used for the bimolecular case [11,13].…”
Section: Generalization Of the Cha/f Methods For The Case Of Three Submentioning
confidence: 99%
“…BSSE) are excluded, while keeping all true charge transfer effects corresponding to real physical interactions between the subsystems. A systematic study [13] showed that the CHA/F scheme can be considered the ultimate solution of the BSSE problem for a pair of weakly bonded molecules at the SCF level of theory.…”
Section: Introductionmentioning
confidence: 99%